Unlocking The Potential Of Process Management - Oktaviani, Desy; Kartomo, Thomas; Ramadhan, Tubagus Guruh; Astuti, Widia; Muslimat, Ade (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Along with the development of information technology, companies and organizations must develop an information system strategy that is based on the business strategy that has been prepared by the company. The purpose of designing a business strategy and information system strategy is to strengthen the power of competitiveness in the technological era by implementing a strategic information system by considering and aligning business strategies that are in accordance with the conditions of the company's strengths. Educational institutions as companies providing educational services must also consider business strategies and information systems strategies to strengthen competition. This research will explain business strategy through process management at private tertiary institutions in region IV having an organizational vision and mission that is designed based on organizational analysis and competition in other PTS in region IV. The vision and mission are analyzed using the strategic option generator (SOG) model to determine the right business strategy. To achieve the vision and mission, an information system strategy must also be designed using the balanced scorecard (BSC) model. Then the resulting business strategy is aligned with the information system strategy to produce an implementation plan that has a competitive advantage with the information system strategy and PTS Fostered business strategy in region IV and translated into a future application portfolio.